Investigating changes in rainfall seasonality across South Africa: 1987–2016. (20th September 2020) - Roffe, Sarah J.; Fitchett, Jennifer M.; Curtis, Christopher J.
Abstract: Changes in rainfall seasonality across South Africa may have detrimental impacts on crop yields and surface water supplies. Despite this, these have rarely been investigated across the South African summer‐, winter‐ and year‐round rainfall zones (SRZ, WRZ and YRZ respectively) using consistent methods. Rainfall seasonality changes are explored here using daily rainfall and temperature records for 1987–2016 from 46 meteorological stations spanning a grid across South Africa. Focusing on comparable methods that statistically define the SRZ, WRZ, YRZ, we apply a ratio of monthly rainfall: temperature and a percentile‐based wet‐season start‐ and end‐date metric, which each provide annual outputs of the degree of seasonality, and the timing, duration, magnitude and intensity of wet‐season rainfall. Although relatively few statistically significant trends are detected, some regional spatial patterns are evident. Trends for most locations across the southwestern Cape and western coast are indicative of a decrease in the strength of seasonality with a reduction in winter wet‐season rainfall, and are broadly consistent with observed and projected poleward dynamics of the southern hemisphere subtropical high‐pressure belt and mid‐latitude westerlies. Trends towards later wet‐season start‐dates together with a reduction in summer wet‐season rainfall amount are prominent across most of the interior and northeastern locations, and may be linked to Hadley cell expansion recorded in recent decades. Along the southern coast, trends towards an increase in the degree of seasonality together with a shorter wet‐season, concentrated around the winter months, are evident. If sustained, the trends quantified present a concerning outlook for continued crop production and water resource management, and thus warrant further investigations on rainfall seasonality shifts and the drivers thereof across southern Africa. Abstract : Changes in rainfall seasonality may have detrimental impacts on rainfall dependent activities (e.g., crop farming) across South Africa. Here, rainfall seasonality changes are investigated across the South African summer, winter and year‐round rainfall zones for 1987–2016. Although, few statistically significant trends were detected, the methods used here provide a basis to (a) investigate trends using consistent methods, comparable primarily through interpretation of the wet‐season length trend direction and (b) enable further monitoring of rainfall seasonality changes and patterns of variability.